The impact of viral tropism and housing conditions on the transmission of three H5/H7 low pathogenic avian influenza viruses in chickens. - Claes, G; S Welby; Thierry van den Berg; Y Van Der Stede; Dewulf, J; Bénédicte Lambrecht; Sylvie Marché (Epidemiol Infect, 2013)
In this study, shedding and transmission of three H5/H7 low pathogenic avian influenza viruses (LPAIVs) in poultry was characterized and the impact of floor system on transmission was assessed. Transmission experiments were simultaneously conducted with two groups of animals housed on either a grid or a floor covered with litter. Transmission was observed for H5N2 A/Ch/Belgium/150VB/99 LPAIV. This virus was shed almost exclusively via the oropharynx and no impact of floor system was seen. Transmission was also seen for H7N1 A/Ch/Italy/1067/v99 LPAIV, which was shed via both the oropharynx and cloaca. A slight increase in transmission was seen for animals housed on litter. H5N3 A/Anas Platyrhynchos/Belgium/09-884/2008 LPAIV did not spread to susceptible animals, regardless of the floor system. This study shows that environmental factors such as floor systems used in poultry barns may act upon the transmission of LPAIVs. However, the level of influence depends on the virus under consideration and, more specifically, its principal replication sites.
Keywords: Animals; Chickens; Hemagglutinin Glycoproteins, Influenza Virus; Housing, Animal; Influenza A virus; Influenza in Birds; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Viral; Viral Tropism